Pengaruh Model Pembelajaran Quantum Teaching Terhadap Hasil Belajar Siswa Pada Materi Operasi Himpunan - Rosiana Jupri; Perry Zakaria; Majid Majid; Resmawan Resmawan; Dewi Rahmawaty Isa (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2022)
This study aims to determine the effect of the Quantum Teaching learning model on student learning outcomes. This research was conducted at a junior high school in Bone Bolango. The research model is an experimental research that uses a posttest control group design consisting of 2 samples, namely, the experimental class and the control class. The sample was selected by a simple random sampling technique involving 24 students for the experimental class and 23 students for the control class. The results showed differences in student learning outcomes taught by the Quantum teaching-learning model and the direct learning model on set operations material. This is indicated by the average value of student learning outcomes in the set operation material of the experimental class is higher than the control class.